2005
DOI: 10.1073/pnas.0508599102
|View full text |Cite
|
Sign up to set email alerts
|

Impaired involution of mammary glands in the absence of milk fat globule EGF factor 8

Abstract: During the involution of mammary glands, epithelial cells undergo apoptosis and are cleared for the next cycle of lactation. The clearance of apoptotic epithelial cells is mediated by neighboring epithelial cells and by macrophages that migrate into the mammary glands. Here, we report that milk fat globule EGF factor 8 (MFG-E8), a secreted glycoprotein that binds to apoptotic cells by recognizing phosphatidylserine, was expressed by epithelial cells and macrophages in mammary glands and was involved in engulfm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 36 publications
6
119
0
Order By: Relevance
“…Of note, plasminogen-deficient mice display delayed involution of the mammary glands (24,25). This process is closely linked to apoptotic cell removal and comparably impaired in mice lacking the engulfment factor MFG-E8 (26). Further studies will help to elucidate whether plasminogen deficiency is associated with defects in corpse clearance and the onset of chronic inflammation and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, plasminogen-deficient mice display delayed involution of the mammary glands (24,25). This process is closely linked to apoptotic cell removal and comparably impaired in mice lacking the engulfment factor MFG-E8 (26). Further studies will help to elucidate whether plasminogen deficiency is associated with defects in corpse clearance and the onset of chronic inflammation and autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, functionally blocking antibodies against MFG-E8 potentiated the effects of chemotherapeutic agents on experimental melanomas, colon carcinomas and lymphomas (Jinushi et al, 2009). In the mammary gland, MFG-E8 expression increases during pregnancy, lactation and subsequent mammary gland involution (Oshima et al, 1999;Hanayama and Nagata, 2005). It was demonstrated that MFG-E8 is required for mammary gland branching morphogenesis (Ensslin and Shur, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…The binding of MFG-E8 to integrins on macrophages and to phosphatidylserine and phosphatidylethanolamine residues on apoptotic cells establishes intercellular interactions that promote the subsequent engulfment of apoptotic cells (Hanayama et al, 2002(Hanayama et al, , 2004. Similarly, MFG-E8 is required for the removal of apoptotic cells by mammary epithelial cells during mammary gland involution (Atabai et al, 2005;Hanayama and Nagata, 2005). MFG-E8 binding to integrins regulates a variety of signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, this study dealt with the functional p63 proteins localized to undifferentiated keratinocytes in the basal layer of stratified epithelia and in carcinomas derived from the stage. MFG-E8-L, the mouse-specific long isoform, having a Pro/Thr-enriched domain, facilitates phagocytosis of apoptotic cells by macrophages as demonstrated by recent studies with MFGE8-deficient mice (Hanayama et al, 2002;Hanayama and Nagata, 2005). However, the other isoform, MFG-E8-S, lacking the phagocytosisfacilitating activity is more ubiquitously, abundantly expressed (Watanabe et al, 2005) and expected to facilitate various types of cell-cell interactions.…”
Section: Mfge8mentioning
confidence: 99%